Warrior up! youth leader - Finch, David (Producer and director); Finch, David (Producer and director); Finch, David (Producer and director); Marovitch, Maureen; Marovitch, Maureen (Picture This Productions, 2024)
Warrior Up! is a documentary series that follows Indigenous youth across Turtle Island who are standing up and making change, transforming their communities, their lands and their lives for the better. Episode 6: Hailey Rose, age 19, is the Indigenous youth representative for the FSIN (The Federation of Sovereign Indigenous Nations) and the AFN (The Assembly of First Nations), representing youth across Saskatchewan and Canada. The topic closest to her heart is mental health - and we see that in action at a dynamic wellness workshop where she helps teens balance all four parts of the medicine wheel. But Hailey has an even bigger event coming up: organizing a youth powwow. It turns out her mother is also excited about the powwow and what will be her first time wearing a ribbon skirt - thanks to Hailey's encouragement. Host Joel Oulette travels to meet Hailey's family and learns how she is bringing Plains Cree culture and language back into their home after it was lost for a generation. He even gets a lesson in Cree himself, relearning some of his own language. And then they head off to the powwow!